Synthesis and biomedical applications of graphitic carbon nitride quantum dots. Issue 36 (4th September 2019) - Liu, Hongji; Wang, Xingyu; Wang, Hui; Nie, Rongrong
Abstract : This review summarizes the synthetic methods and addresses current applications and future perspectives of graphitic carbon nitride quantum dots in the biomedical field. Abstract : Graphitic carbon nitride quantum dots (g-CNQDs) have attracted much attention for biomedical applications by virtue of their good biocompatibility, stable fluorescence, high quantum yield, and nontoxicity. On the basis of understanding the intrinsic properties and structural features in the intriguing system, enormous efforts have been devoted to optimizing synthetic methods and structures of g-CNQDs. A vast number of studies have also been pursued to discuss the potential applications of g-CNQDs in biomedical areas for biosensing, bioimaging, drug delivery and theranostics. In this review, we summarize the recent advances and applications and address the future challenges and opportunities of these g-CNQDs in the biomedical field.